Competency-Based Village Development: Skill Mapping Training and Productive Career Planning for Village Youth in Labuhanbatu - Siti Lam'ah Nasution; Eva Julyanti; Sakinah Ubudiyah Siregar; Yudi Prayoga; Aulia Indra; Fadzil Hanafi Asnora (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Rural youth play a strategic role in supporting local economic development. However, many young people in rural areas still face limitations in identifying their personal potential, mapping competencies, developing career plans, and connecting their skills with productive opportunities in their local environment. This community service program aimed to strengthen the capacity of rural youth in Labuhanbatu Regency through skill mapping and productive career planning training. The program applied a participatory training approach consisting of preliminary observation, coordination with village partners, module preparation, pre-test implementation, material delivery, competency mapping practice, career planning exercises, group discussions, post-test, and program evaluation. The target participants included rural youth, youth organization members, senior high school or vocational school graduates, village-based university students, and prospective young entrepreneurs. The results indicated that participants improved their understanding of self-potential, work competencies, soft skills, career planning, and local economic opportunities. Participants were also able to develop individual competency maps and formulate short-, medium-, and long-term career action plans. This program contributes to rural human resource development through a competency-based mentoring model that can be further developed into a village talent bank, youth business incubation program, and continuous training agenda for youth organizations and village governments.